2016
DOI: 10.31235/osf.io/2y2xp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increases in Sex with Same-Sex Partners and Bisexual Identity Across Cohorts of Women (but Not Men)

Abstract: *Abstract:**We use data from the 2002-2013 National Surveys of Family Growth toexamine change across U.S. cohorts born between 1966 and 1995 in whetherindividuals have had sex with same-sex partners only, or with both men andwomen, and in whether they have a bisexual or gay identity. Adjusted forage, race/ethnicity, immigrant status, and mother’s education, we findincreases across cohorts in the proportion of women who report a bisexualidentity, who report ever having had sex with both sexes, or who reporthavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 10 publications
(17 reference statements)
6
35
0
Order By: Relevance
“…Past studies have found gender differences in trends, such that the increase in same-sex sexual behavior has been more pronounced among women. Butler (2005), Turner et al (2005) and England et al (2016) all suggest significant recent increases of same-sex sex across recent cohorts of women, but they find much less or even no cohort change among men. Why might we expect trends in same-sex sexual behavior to differ by gender?…”
Section: Do Trends Vary By Gender?mentioning
confidence: 97%
See 2 more Smart Citations
“…Past studies have found gender differences in trends, such that the increase in same-sex sexual behavior has been more pronounced among women. Butler (2005), Turner et al (2005) and England et al (2016) all suggest significant recent increases of same-sex sex across recent cohorts of women, but they find much less or even no cohort change among men. Why might we expect trends in same-sex sexual behavior to differ by gender?…”
Section: Do Trends Vary By Gender?mentioning
confidence: 97%
“…This conclusion is suspect given that the techniques they used, proposed by , have been shown via simulation not to identify cohort trends in some cases where they exist in artificially generated data . The only multivariate analysis of cohort change in sex with same-sex partners is a study by England, Mishel and Caudillo (2016), which used NSFG data. Among women, they found cohort increases in reports of bisexual identity, of sex with both sexes, and of sex with women only.…”
Section: Past Research On Change In Sex With Same-sex Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, studies show that women are generally more sexually fluid than men in terms of engaging in same-sex sexual behavior. Both large, survey-based quantitative studies and qualitative studies using smaller samples show that more women report having same-sex sex and same-sex attraction than men (e.g., Diamond 2008Diamond , 2014England et al 2016;Gates 2011;Laumann et al 1994;Mishel et al 2018;Mishel n.d.). Research has also shown that same-sex sexual behavior is sometimes strategically mobilized by heterosexual-identifying women who seek to garner attention from men (e.g., Hamilton 2007).…”
Section: Policing Sexual Orientation and The "One-act Rule"mentioning
confidence: 99%
“…New data from the National Survey of Family Growth (NSFG) suggest that the proportion of young women who identify as bisexual is increasing among younger cohorts. 24 Using data from The National Longitudinal Study of Adolescent to Adult Health, a nationally representative survey of U.S. adolescents grades 7 to 12 found that 15% of females identified as a SMW. 25 Additionally, data from the 2015 Youth Risk Behavior Survey, a national school-based survey of 9th to 12th graders, found that 2.0% of females identified as gay/ lesbian and 9.8% as bisexual.…”
Section: Estimates Of Smw In the United Statesmentioning
confidence: 99%